2022
DOI: 10.26555/eshr.v4i2.5341
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Diabetes Mellitus Patients in Indonesian Chronic Disease Management Program (Prolanis)

Abstract: Background: International Diabetes Federation (IDF) data shows that the increasing prevalence of diabetes mellitus worldwide is still happening and is a significant global health challenge. Patients with diabetes mellitus tend to have a poorer quality of life than those without a chronic disease. This study aims to obtain an overview of the quality of life of patients with diabetes mellitus. Method: This research was a quantitative descriptive study with a cross-sectional approach, conducted in July–October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Different results by Ladyani et al and Mukti showed there was no significant relationship between PROLANIS participation and HbA1c (p=0.389 (Mukti, 2020)) dan (p1,000, OR 1,400 (Ladyani et al, 2020)). The results also show that the number of DM participants who take PROLANIS who have QoL in the excellent category is increasing (>50%) (Dewi & Faozi, 2023;Marwati et al, 2022;Noviyantini et al, 2020). There is a significant relationship between active participation in PROLANIS and QoL (p.000, r0.731) (Wicaksono & Fajriyah, 2018).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Different results by Ladyani et al and Mukti showed there was no significant relationship between PROLANIS participation and HbA1c (p=0.389 (Mukti, 2020)) dan (p1,000, OR 1,400 (Ladyani et al, 2020)). The results also show that the number of DM participants who take PROLANIS who have QoL in the excellent category is increasing (>50%) (Dewi & Faozi, 2023;Marwati et al, 2022;Noviyantini et al, 2020). There is a significant relationship between active participation in PROLANIS and QoL (p.000, r0.731) (Wicaksono & Fajriyah, 2018).…”
Section: Resultsmentioning
confidence: 95%
“…The second role that many people get from PROLANIS is maintaining and reducing HbA1c (Ahmad et al, 2017;Alkaff et al, 2021;Ladyani et al, 2020;Mukti, 2020;Setyawan et al, 2020;Syuadzah, 2017). Furthermore, PROLANIS also has a role in improving the quality of life of DM patients (Anwar et al, 2020;Dewi & Faozi, 2023;Marwati et al, 2022;Noviyantini et al, 2020;Wicaksono & Fajriyah, 2018) Table 2 General Characteristics of Articles…”
Section: Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologically, foot disorders in diabetic patients reach a significant number, with numbers 8% to 52.0% occurrence in diabetic population, raising concerns among healthcare professionals to prevent such incidents by providing optimal promotive and preventive services (Gamboa-Antiñolo, 2023). However, the quality of healthcare services often faces challenges, and the intended goals may not be fully achieved (Marwati et al, 2022). One of the current practices is diabetic foot exercises for patients.…”
Section: Introductionmentioning
confidence: 99%